Effect of Tm addition on the precipitation, mechanical, and electrical properties of a Cu–Ti alloy during aging - Nian Hong; Yumin Liao; Huiming Chen; Chenyang Zhou; Weibin Xie; Bin Yang; Hang Wang (Journal of Materials Research and Technology, 2025)
The study examines the impact of Tm addition on the microstructural change and precipitation behaviour in Cu-3.5Ti alloy subjected to cold rolling and aging. The findings demonstrate that spinodal and dislocation strengthening emerge as the primary strengthening mechanisms in both Tm-added and Tm-free Cu–Ti alloys during the peak-aging stage, resulting in an impressive strength exceeding 900 MPa. However, with prolonged aging, a significant softening occurs in the alloys, attributed to the recovery of dislocations, a decrease in Ti solute atoms, and the growth of DP colonies. The Tm addition effectively suppresses the discontinuous precipitation. The Tm-added alloy demonstrates greater strength than that of the Tm-free alloy for the same aging time, primarily due to the lower volume fraction of the DP colonies. Additionally, the impurity scattering effect within the DP colony is weaker than that in the deformed grains. The inhibiting effect of Tm on discontinuous precipitation results in a slower growth rate of the DP colonies, which facilitates a slower increase in electrical conductivity in the Tm-added alloy compared to the Tm-free alloy.